New ultrasonic array structure for fixed condition monitoring in solid media - Hayward, G.; McNab, A.; Cochran, A. (Ultrasonics, 1989)
An ultrasonic array structure consisting of a monolithic piezoelectric plate attached to a separate electrode assembly via epoxy bonding has been developed for monitoring the condition of solid test subjects using a directly coupled configuration. This paper describes the new structure and outlines the techniques which have been developed for the convenient and reliable construction of prototype high frequency linear arrays, using minimal equipment. Typical array characteristics including back wall pulse-echo responses, element impedance measurements and element directivity are presented, together with appropriate comparative theoretical results. The image quality attainable using the structure is demonstrated by experimental results obtained from a selection of test pieces.